The Influence of High-Strength Bolts Stiffening on Flange Connection Behaviour - MAJOR, Izabela; MAJOR, Maciej; KULIŃSKI, Krzysztof (Engineering Transactions, 2019)
Flange connections can commonly be seen in advertising board structures, which are subjected to wind loading. Depending on the structure’s geometry, additional torsion forces should be taken into account. In this paper the static behaviour of a flange connection with high-strength bolts under torsion load has been discussed. The numerical analysis concerns two cases: a flange connection subjected only to a high-strength bolts prestressing load and a flange connection subjected to both – bolts prestressing force and torsion moment. The stated boundary problem has been solved with the use of SolidWorks software. The obtained numerical results show good agreement with the analytical method.